Halls Reservation Application for University Lectures - Shalgom, Walid S. M. (2009)
The main objective of this study is to design and develop a WAP Halls Reservation Application for University Lecturers to searching the availability of halls, the time of hall reserve to develop a system of the Hall Reservation System. The prototype would have two functions; one function is for administrator of University Utara Malaysia by using Web application and the other function is for staffs and lecturers by using WAP application. There are several software's used in this study such as UML to design the requirement of the system by draw out the use case diagram, and JSP as programming language to build the system and SPSS to analysis the data after made questionnaire with the lecturer which they test the system. The Wireless Application Protocol (WAP) technologies have been used in this application has enable lecturer to make reserve through mobile telephones.